(untitled) (Journal of Engineering, 2012)
The evolution in materials’ technology in the last decades resulted in interesting projects that aimed at preserving the environment and energy and reduce pollution. They have been taken the principles of environmental design as a basis for architectural thought, starting from the early stages of the design process ending in choosing appropriate building materials to achieve sustainable buildings, but these trying are limited in our local environment and there isn’t demanded seriousness. The research problem emerges in the ignorance of the environmental aspect (ecological system) when selecting building materials during design process to achieve sustainable buildings. The aim of this research is revealing the mechanisms of selecting building materials to improve the functional performance and reduce the negative effects on the environment and preserve its resources and the ecological systems as much as possible according to the following indicators: Embodied energy, recycling, durability; to assist architects and specific engineers in making decisions that have a significant impact in achieving sustainable buildings in the local environment and the possibility of application in Iraq .